2003
DOI: 10.1097/01.mbc.0000061290.28953.57
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of disseminated intravascular coagulation (DIC) progresses at a different rate in tissue factor-induced and lipopolysaccharide-induced DIC models in rats

Abstract: Tissue factor (TF) and lipopolysaccharide (LPS) are frequently used to induce disseminated intravascular coagulation (DIC) in experimental animal models. Although the pathophysiology of DIC may differ depending on which agent is used for induction, previous studies on models of DIC have not distinguished which DIC-inducing agent was used. In the present paper, we evaluate the characteristics of TF-induced and LPS-induced DIC using two types of DIC models, with special reference to selected hemostatic parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…Coagulopathy may worsen during the first few days after cooling and result in bleeding diathesis (11,78,238). Bleeding diathesis (also known as consumptive coagulation) is characterized by excessive blood loss as the consumption of platelets and coagulation proteins outpaces production (20,28). Heat stroke patients may experience hemorrhagic complications such as prolonged bleeding from venipuncture sites or other areas, including the gums (183).…”
Section: Hematologic Disturbancesmentioning
confidence: 99%
“…Coagulopathy may worsen during the first few days after cooling and result in bleeding diathesis (11,78,238). Bleeding diathesis (also known as consumptive coagulation) is characterized by excessive blood loss as the consumption of platelets and coagulation proteins outpaces production (20,28). Heat stroke patients may experience hemorrhagic complications such as prolonged bleeding from venipuncture sites or other areas, including the gums (183).…”
Section: Hematologic Disturbancesmentioning
confidence: 99%
“…Early in heat stroke, widespread activation of coagulation stimulates excess deposition of fibrin in the arterioles and capillaries along with platelet aggregation that leads to microvascular thrombosis. Although rapid cooling of the heat stroke patient may normalize fibrinolysis, coagulation often persists until platelets and coagulation proteins are consumed at a faster rate than they are produced (2,4). Consumptive coagulation may lead to excessive, prolonged bleeding from multiple tissue sites (e.g., venipuncture sites, gums) and is associated with fatal outcome (46).…”
Section: The Systemic Inflammatory Responsementioning
confidence: 99%
“…This profibrinolytic response is almost immediately followed by suppression of fibrinolytic activity. This is caused by a sustained increase in the plasma level of plasminogen activator inhibitor in LPS-induced DIC (1)(2)(3)(4)(5). Activation of coagulation and impairment of fibrinolysis is mediated by cytokines, such as TNF, IL-1, and IL-6, in LPS-induced DIC (1-4).…”
Section: Discussionmentioning
confidence: 98%
“…which clinically resembles DIC due to sepsis. The other is a TF-induced model of DIC, which clinically resembles DIC in the setting of acute leukemia (5,21,22). The following features were common to both models examined in this study: Markedly increased plasma TAT levels were observed, as were significantly depressed plasma fibrinogen levels and platelet counts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation